Wind exposure and sediment type determine the resilience and response of seagrass meadows to climate change. Issue Volume 67:Issue S1(2022)Special issue (17th June 2021) - de Smit, Jaco C.; Bin Mohd Noor, Muhammad S.; Infantes, Eduardo; Bouma, Tjeerd J.
Abstract: Seagrasses and bare sediment represent alternative stable states, with sediment resuspension being a key driver of system stability via the Seagrass–Sediment–Light (SSL) feedback. We explore the SSL feedback by quantifying the sediment stabilization by seagrass, and using these measurements to calculate under which conditions seagrass ends up in a turbid environment. We quantified in‐situ sediment resuspension velocity thresholds ( u cr ) for Zostera marina growing in medium to fine sand, using a field flume inducing near‐bed wave motion. u cr was determined for full length shoots, shoots clipped to 0.08 m, and removed shoots. We found that rhizomes did not influence u cr of the top sediment layer. Overall, u cr was linearly related to blade area, which became independent for sediment type when normalizing u cr for the resuspension threshold after shoot removal. Comparing measured u cr against natural wave conditions showed that the seagrass meadow at the study site is currently stable. Exploring the effects of changing hydrodynamic conditions revealed that effects of increasing storminess has limited influence on sediment resuspension and thus the SSL‐feedback. Increasing mean wind velocity had a stronger influence on SSL‐feedback dynamics by causing more frequent exceedance of u cr . The response of seagrasses to increasing wind pressure depends on bay topography. A fully exposed Z. marina meadow under low initial turbidity pressure trended toward bistability, as turbidity pressure increased mainly on bare sediments. The study site and a fully exposed Z. marina meadow under high initial turbidity pressure saw an increase in turbidity across all blade areas.